2014
DOI: 10.1177/0300060514548290
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between expression of matrix metalloproteinase-9 and adenylyl cyclase-associated protein 1 in chronic obstructive pulmonary disease

Abstract: This study demonstrated an inverse relationship between CAP1 and MMP-9 expression, and high expression of MMP-9 and low expression of CAP1 in those with COPD compared with the non-COPD group. Overexpression of MMP-9 in lung tissue and its interaction with CAP1 is likely to play a major role in airway obstruction in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
8
1
1
Order By: Relevance
“…Somewhat surprisingly and apparently in contrast to other authors [ 23 , 27 , 34 ] we could not correlate the levels of MMPs measured in bronchial fluid with the presence or absence of COPD. However, taking a closer look in one study [ 27 ], no information was provided regarding the smoking status of the study participants. In another study [ 23 ], which investigated the levels of MMP8, MMP9 and MMP12 in the induced sputum, only MMP8 was higher in symptomatic smokers with COPD Stage GOLD 0 compared to non-symptomatic smokers.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Somewhat surprisingly and apparently in contrast to other authors [ 23 , 27 , 34 ] we could not correlate the levels of MMPs measured in bronchial fluid with the presence or absence of COPD. However, taking a closer look in one study [ 27 ], no information was provided regarding the smoking status of the study participants. In another study [ 23 ], which investigated the levels of MMP8, MMP9 and MMP12 in the induced sputum, only MMP8 was higher in symptomatic smokers with COPD Stage GOLD 0 compared to non-symptomatic smokers.…”
Section: Discussioncontrasting
confidence: 99%
“…MMPs seem to represent important peptides and markers in both, the pathogenesis of lung diseases [ 7 , 9 , 27 , 28 ] and periodontitis [ 5 , 25 , 29 ]. Therefore, in the current study MMP2, aMMP8, MMP9 and MMP12 were measured in the bronchial fluid of 91 patients undergoing elective diagnostic bronchoscopy and these findings correlated with the presence of periopathogenic marker species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 and high levels of MMP-9 and lower levels of CAP1 have been observed in chronic obstructive pulmonary disease. 28 A number of publications have demonstrated that hormone receptors and G protein-coupled receptors (GPCRs) activate MMP-9. [29][30][31] Recent research has also revealed that extracellular amino acids can be sensed by plasma membrane receptors, such as GPRC6A and GPCR T1R1/T1R3, and regulate mTOR.…”
Section: Figurementioning
confidence: 99%
“…Как уже сообщалось выше, в процессах сборки ламеллоподий участвует множество различных белков. Так, например, показано, что экспрессия ММР-9 эпителиальными клетками дыхательных путей связана с экспрессией CAP-1 [68], белка семейства аденилилциклазаассоциированных протеинов (Catabolite Gene Activator Protein, САР), относящихся к актинсвязывающим белкам, которые принимают участие в регуляции актинового цитоскелета и Ras/cAMPсигнального пути. Предполагаемый механизм участия CAP-1 в регуляции подвижности клеток -комплекси-рование с талином (белком, прикрепляющим актин к мембране) и киназой фокальных контактов (FAK) [2,3], активность которой сопряжена с увеличением синтеза MMР [69,70].…”
Section: внеклеточный протеолизunclassified